ANALYSIS OF THE EFFECT OF FINANCIAL RATIOS AND BANK SIZE ON NON-PERFORMING LOANS IN BANKS IN INDONESIA - Erdawati, Lena; Kaswoto, Junet; Hamdani, Hamdani; Perdita, Liska; Sasmita, Djenni (Univesitas Muhammadiyah Tangerang, 2024)
This research was conducted on Conventional Banks Listed on the Indonesia Stock Exchange for the 2017-2021 Period. The study aims to determine the effect of financial ratios, and bank size on non-performing loans in conventional banks listed on the Indonesia Stock Exchange for the 2017-2021 period. The data collection method uses purposive sampling. Based on the criteria set, 35 companies were obtained. The type of data used is secondary data obtained from the website of each company. The measuring tool of this study uses Eviews 9. The analysis method used is panel data regression. Based on the results of the study: There is no effect of Loan to Deposit Ratio on Non-Performing Loans. There is no effect of Capital Adequancy Ratio on Non-Performing Loans. There is a positive effect of Operating Costs on Operating Income on Non-Performing Loans. There is no influence of Bank Size on Non-Performing Loans. This research is expected to benefit accounting in the implementation of financial management accounting learning. This research is also expected to contribute in the form of understanding for business actors in making investment decisions in the banking sector.